Hierarchical novel NiCo2O4/BiVO4 hybrid heterostructure as an advanced anode material for rechargeable lithium ion battery. (17th August 2020) - Tamboli, Mohaseen S.; Jadhav, Harsharaj S.; Patil, Deepak R.; Shaikh, Asiya F.; Patil, Santosh S.; Seo, Jeong Gil; Choi, Hyosung; Gosavi, Suresh W.; Kale, Bharat B.
Summary: Hybrid metal oxide heterostructures have been considered as ideal and potential anode materials for lithium ion batteries (LIBs) due to their better electrochemical performances, such as reversible capacity, structural stability and electronic conductivity. Herein, we have demonstrated synthesis of NiCo2 O4 /BiVO4 heterostructures by simple hydrothermal strategy to construct hybrid x NiCo2 O4 /(1– x )BiVO4 heterostructures with four selected compositions, that is, x = 10%, 20%, 30% and 40%. XRD shows the phases of NiCo2 O4 and BiVO4 and FE‐SEM data revealed strong interface coupling between NiCo2 O4 nanowires and BiVO4 dendrites. Upon testing for electrochemical properties, the optimized composition of 30%NiCo2 O4 ‐70% BiVO4 showed higher reversible capacity of 408.6 mAh/g at a constant current rate of 0.5 A/g after 1000 cycles with columbic efficiency around 99% suggesting potential electrode material for high‐performance LIBs. The higher capacity is mainly attributed to the large surface area which can provide more channels and locations for fast Li ion intercalation/de‐intercalation into electrode materials. Additionally, improved Li ion storage capacity with superior rate capability of BN‐30 electrode could be attributed to its lower charge‐transfer resistance. The dendritic and nanowire heterostructure novel system with good stable capacity for LIBs is hitherto unattempted. Abstract : The hierarchical architecture NiCo2 O4 /BiVO4 heterostructures synthesized by simple hydrothermal strategy was assessed to construct hybrid x NiCo2 O4 /(1– x )BiVO4 heterostructures has been demonstrated for the first time with four selected compositions of x = 10%, 20%, 30% and 40%. The optimized composition of 30%NiCo2 O4 ‐70% BiVO4 (BN‐30) showed higher reversible capacity of 408.6 mAh/g at a constant current rate of 0.5 A/g after 1000 cycles with columbic efficiency around 99% suggesting potential electrode material for high‐performance LIBs.